Memory-guided reaching in a patient with visual hemiagnosia. (June 2016) - Cornelsen, Sonja; Rennig, Johannes; Himmelbach, Marc
Abstract: The two-visual-systems hypothesis (TVSH) postulates that memory-guided movements rely on intact functions of the ventral stream. Its particular importance for memory-guided actions was initially inferred from behavioral dissociations in the well-known patient DF. Despite of rather accurate reaching and grasping movements to visible targets, she demonstrated grossly impaired memory-guided grasping as much as impaired memory-guided reaching. These dissociations were later complemented by apparently reversed dissociations in patients with dorsal damage and optic ataxia. However, grasping studies in DF and optic ataxia patients differed with respect to the retinotopic position of target objects, questioning the interpretation of the respective findings as a double dissociation. In contrast, the findings for reaching errors in both types of patients came from similar peripheral target presentations. However, new data on brain structural changes and visuomotor deficits in DF also questioned the validity of a double dissociation in reaching. A severe visuospatial short-term memory deficit in DF further questioned the specificity of her memory-guided reaching deficit. Therefore, we compared movement accuracy in visually-guided and memory-guided reaching in a new patient who suffered a confined unilateral damage to the ventral visual system due to stroke. Our results indeed support previous descriptions of memory-guided movements' inaccuracies in DF. Furthermore, our data suggest that recently discovered optic-ataxia like misreaching in DF is most likely caused by her parieto-occipital and not by her ventral stream damage. Finally, multiple visuospatial memory measurements in HWS suggest that inaccuracies in memory-guided reaching tasks in patients with ventral damage cannot be explained by visuospatial short-term memory or perceptual deficits, but by a specific deficit in visuomotor processing.